Ultrasound-Assisted Synthesis of N -Acylcyanamides and N -Acyl-Substituted Imidazolones from Carboxylic Acids by Using Trichloroisocyanuric Acid/Triphenylphosphine - Wong Phakhodee (2020)
© 2020 Georg Thieme Verlag. All rights reserved. A convenient ultrasound-assisted one-pot synthesis of N -acylcyanamides starting from readily available carboxylic acids and sodium cyanamide has been developed. Upon activation in the presence of trichloroisocyanuric acid (TCCA) and triphenylphosphine, a range of carboxylic acids was converted into N -acylcyanamides in good to excellent yields within 10 minutes at room temperature without base. Remarkably, N -acyl-substituted imidazolones were readily accessible through guanylation-cyclization of the in situ generated N -acylcyanamides.